The World Bank and the poorest countries : support for development in the 1990 - World Bank. (Washington, D.C. : World Bank, 1994)
This report summarizes how World Bank policies and programs in the poorest countries have become focused on the overarching objective of poverty reduction during the FY91 - 93, as recommended in the IDA( Agreement
Includes bibliographical references.
osc 31/07/2019
Loans
Keywords: Structural adjustment (Economic policy); Debts, External; Economic assistance; Developing countries